Difficulties in collaborations between academia and industry: An analysis of the Austrian context - Meha, Arbresha; Loku, Afrim (Edelweiss Applied Science and Technology, 2025)
Collaborations between academia and industry represent an evolving trend aimed at fostering innovation and promoting economic progress. However, establishing and managing such partnerships often present various challenges. This study offers insights into the most common difficulties encountered in collaborations between academia and industry, based on data collected from 52 semi-structured interviews with management and researchers working across 10 public universities, 10 universities of applied sciences, and 15 companies in Austria. The findings reveal that numerous obstacles can hinder effective collaboration. These challenges include issues related to building partnership expectations, such as defining and aligning objectives, goals, priorities, processes, and the focus of collaboration. Additionally, partners often face difficulties related to resource allocation, roles, and responsibilities. Time constraints also pose significant challenges, as industry tends to have a short-term perspective focused on research and implementation, whereas researchers emphasize careful planning, analysis, and validation of findings. Insufficient communication between partners further complicates collaboration efforts, creating barriers to success. Our analysis suggests that understanding the needs, strengths, and limitations of each partner is crucial for establishing and managing successful academic-industry partnerships.